The thank you economy - Vaynerchuk, Gary. (New York : Harper Business, 2011)
Gary Vaynerchuk contends that the people and companies harnessing the word-of-mouth power provided by multiplatform media -- those that can shift their outlook and operations to be more customer-aware and fan-friendly -- will pull away from the pack and profit in today's markets.
Includes bibliographical references.
BBA, MBA, EMBA.
Keywords: Customer relations; Social media; Branding (Marketing); Internet marketing; Management